Gambaran kejadian kurang Energi Kronis (KEK) ibu hamil di wilayah kerja BLUD Puskesmas Kandai Kota Kendari Tahun 2023 - Mochtar, Febriana (NHM PRESS, 2024)
Chronic energy deficiency (CED) is a nutritional condition caused by long-term inadequate energy intake. In pregnant women, CED can lead to significant health complications for both the mother and the fetus. CED is assessed by measuring the upper arm circumference, with values less than 23.5 cm indicating deficiency. This research was performed to examine the prevalence of CED among pregnant women in the work area of Kandari Health Center from January to April 2023. This quantitative research was administered using the descriptive survey approach, involving 96 pregnant women who attended antenatal check-ups during the specified period. The findings revealed that 19 pregnant women (19.8%) experienced CED, where 11 women (11.5%) were under the high-risk age category. Significant nutritional status issues among pregnant women were identified, as evidenced by the prevalence of chronic energy deficiency (CED) and the presence of pregnancies in high-risk age groups. Effective strategies are required to enhance maternal nutrition, including increasing awareness among pregnant women about the importance of quality food intake and providing supplementary food to mitigate nutritional deficiencies.